2016
DOI: 10.1097/md.0000000000002692
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cut-Off Values of Lymph Node Ratio Predicting Recurrence in Papillary Thyroid Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
1
32
0
1
Order By: Relevance
“…Ryu et al report that a LN ratio >0.65 is a significant predictor of recurrence after prophylactic CND in pN1a patients . The optimal cutoff values for LN ratio may require further definition in central and lateral LNs . The adequacy of LN yield for PTC staging may also need to be re‐assessed to enable standardization .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryu et al report that a LN ratio >0.65 is a significant predictor of recurrence after prophylactic CND in pN1a patients . The optimal cutoff values for LN ratio may require further definition in central and lateral LNs . The adequacy of LN yield for PTC staging may also need to be re‐assessed to enable standardization .…”
Section: Discussionmentioning
confidence: 99%
“…30 The optimal cutoff values for LN ratio may require further definition in central and lateral LNs. 31 The adequacy of LN yield for PTC staging may also need to be reassessed to enable standardization. 32 The present study also showed that a higher number of LNs and the LN ratio were significantly associated with post-treatment recurrence and increased likelihood of ENE.…”
Section: Prediction Of Nodal Metastasis and Enementioning
confidence: 99%
“…proposed LNR as an alternative to pN staging in node‐positive breast cancer . In contrast, the relationship between LNR and oncologic outcomes in PTC has focused only on tumor recurrence , not mortality. One study proposed total LNR as a prognostic factor of PTC using the SEER (Surveillance, Epidemiology, and End Results) dataset , but the authors did not adjust for the location of metastatic LNs, which is the most important criteria in N staging of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PTC is the most common histological type of thyroid cancer and elicits good therapeutic response to surgery and radioiodine treatment. For patients with advanced stage PTC, LNR has been suggested to be useful to predict prognosis by several studies [ 21 , 22 ]. We confirmed that LNR was associated with DSS in patients with advanced stage by univariate and multivariate Cox regression analysis ( P < 0.05), illustrating the contribution of LNR to the risk of disease specific death.…”
Section: Discussionmentioning
confidence: 99%